2018
DOI: 10.1002/ange.201802521
|View full text |Cite
|
Sign up to set email alerts
|

Multielectron‐Transfer‐based Rechargeable Energy Storage of Two‐Dimensional Coordination Frameworks with Non‐Innocent Ligands

Abstract: The metallically conductive bis(diimino)nickel framework (NiDI), an emerging class of metal-organic framework (MOF) analogues consisting of two-dimensional (2D) coordination networks,w as found to have an energy storage principle that uses both cation and anion insertion. This principle gives high energy led by am ultielectron transfer reaction:I ts specific capacity is one of the highest among MOF-based cathode materials in rechargeable energy storage devices,with stable cycling performance up to 300 cycles.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…The X-ray crystal structure analysis of 5 revealed that the coordination bonds established a 2D network with a cavity ~12 Å in size. Compared with the previously reported MOFs used as the active materials [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and Stokes radii of the Li ion (~4.8 Å in propylene carbonate) [ 58 ], the cavity in the 2D coordination sheet of 5 is large enough to be used as a space for storage and transfer of Li ions. On the other hand, in the π-stacking structure, the sheets stacked non-parallelly, and the coordinating sites in the next sheet partially cover the cavity ( Figure 8 a) and, thus, the 1D channel narrowed to ~6 Å ( Figure 5 b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The X-ray crystal structure analysis of 5 revealed that the coordination bonds established a 2D network with a cavity ~12 Å in size. Compared with the previously reported MOFs used as the active materials [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and Stokes radii of the Li ion (~4.8 Å in propylene carbonate) [ 58 ], the cavity in the 2D coordination sheet of 5 is large enough to be used as a space for storage and transfer of Li ions. On the other hand, in the π-stacking structure, the sheets stacked non-parallelly, and the coordinating sites in the next sheet partially cover the cavity ( Figure 8 a) and, thus, the 1D channel narrowed to ~6 Å ( Figure 5 b).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a cavity in the coordination network can be utilized as a space for Li-ion to increase the efficiency and speed of giving and receiving of electrons in charge–discharge processes. From these viewpoints, redox-active MOFs were widely investigated as cathode and anode active materials of LIB [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The uneven distribution, gradual consumption, rarity, and increasing price of Li resources themselves to some great extent limit the large‐scale application of LIBs in the near future. Investigations for alternative rechargeable batteries based on earth‐abundant elements have become even more significant 80 . Na‐ion batteries (SIBs) are attractive and promising substitute for LIBs because of the abundant sodium species and their high energy storage properties that can compete with LIBs 81 .…”
Section: Conductive Mofs Towards Electrochemical Energy‐related Applimentioning
confidence: 99%
“…This mechanism is widely accepted in recent literatures. [17] Some reports [14,42,58] also suggested that Ni(opda) 2 can lose two electrons,l eading to [Ni II (opda) 2 ] 2+ (Supporting Information, Figure S23). This claim makes it plausible that Ni-BTAc an even undergo four-electron redox reactions during cycling.…”
Section: Forschungsartikelmentioning
confidence: 99%